2012
DOI: 10.1007/s10897-012-9504-z
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and Practices Among Internists Concerning Genetic Testing

Abstract: Many questions remain concerning whether, when, and how physicians order genetic tests, and what factors are involved in their decisions. We surveyed 220 internists from two academic medical centers about their utilization of genetic testing. Rates of genetic utilizations varied widely by disease. Respondents were most likely to have ordered tests for Factor V Leiden (16.8%), followed by Breast/Ovarian Cancer (15.0%). In the past 6 months, 65% had counseled patients on genetic issues, 44% had ordered genetic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
144
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 147 publications
(148 citation statements)
references
References 34 publications
4
144
0
Order By: Relevance
“…53 Ten studies examined PCPs' self-reported subjective or perceived knowledge. 33,37,[42][43][44][45]47,50,51,55 Although there was no overlap in measures, studies consistently reported a lack of PCPs' confidence in their genetic testing-related knowledge. For example, in a cross-sectional survey of 1311 family practitioners, 54% were not confident in their knowledge of genetic testing in primary care including testing for breast cancer risk.…”
Section: Knowledge Of Genetic Tests For Cancer Riskmentioning
confidence: 99%
See 4 more Smart Citations
“…53 Ten studies examined PCPs' self-reported subjective or perceived knowledge. 33,37,[42][43][44][45]47,50,51,55 Although there was no overlap in measures, studies consistently reported a lack of PCPs' confidence in their genetic testing-related knowledge. For example, in a cross-sectional survey of 1311 family practitioners, 54% were not confident in their knowledge of genetic testing in primary care including testing for breast cancer risk.…”
Section: Knowledge Of Genetic Tests For Cancer Riskmentioning
confidence: 99%
“…45 In another cross-sectional survey of 1209 Oregon clinicians, 83% of primary care providers and 76% of obstetricians/gynecologists reported that they were Bnot at allô r Bsomewhat^(vs. Bmoderately^or Bvery^) confident in their knowledge of colorectal cancer genetics. 37 Seven studies also evaluated PCPs' knowledge in terms of their comfort level with discussing aspects of cancer genetic testing with patients, 33,40,43,44,46,53,56 with results suggesting that PCPs rarely felt prepared for the task of counseling patients about genetic testing. For example, a survey of 50 obstetricians/ gynecologists found that 74% did not feel comfortable counseling patients about available genetic testing for Lynch syndrome, and 76% did not feel comfortable counseling patients about such testing criteria.…”
Section: Knowledge Of Genetic Tests For Cancer Riskmentioning
confidence: 99%
See 3 more Smart Citations